No more Pygmalion: Teachers’ expectations, mattering and self-efficacy in the online classroom - Jun Ren Tung; Jin Chin Hee; Kususanto Ditto Prihadi (Institute of Advanced Engineering and Science, 2022)
Studies before the outbreak reported that lecturers' and teachers’ expectancy were observable to the students from their classroom behavior and, in turn, affect the students' educational self-efficacy (ES). Our study was conducted to investigate whether the aforementioned finding still holds in the compulsory online learning environment during the COVID-19 pandemic. Online learning was not the only implication of the social distancing policy during the pandemic, any form of social interactions among university students was affected up to the point that they rely more on social media to obtain social feedback that eventually altered the way they evaluate themselves. Because this phenomenon might lead to the way students develop the sense that they matter to their society societal mattering (SM) we hypothesized that SM would be a stronger predictor of ES than the students’ perception of the educators’ expectancy. Nevertheless, the data we collected from 361 purposively recruited students from universities in Indonesia and Malaysia indicated that their perceptions of teachers’ expectancy were no longer a significant predictor of ES when the social mattering was controlled for. Further implications, limitations, and suggestions are discussed.